Self-objectification in women causes, consequences, and counteractions - Calogero, Rachel M.; Tantleff-Dunn, Stacey; Thompson, J. Kevin
"Modern industrialized society chronically and pervasively objectifies the female body, and many women have come to view themselves through the lens of an external observer, habitually monitoring their own appearance whether in public or private settings. Given the negative effects associated with self-objectification-such as body shame, appearance anxiety, depression, and disordered eating-an empirically based approach to researching and counteracting self-objectification is critical. This book integrates recent research developments and current clinical knowledge on self-objectification in women. Using Barbara L. Fredrickson and Tomi-Ann Roberts' objectification theory as a framework, the contributors address various aspects of the theory, including evidence for and causes of self-objectification across the life span, psychological consequences, and associated mental health risks. The book also discusses various scales for measuring self-objectification, as well as approaches to prevent and disrupt this phenomenon. With research from a variety of disciplines-psychology, sociology, anthropology, women's studies, and political science-this book should be read by everyone interested in the well-being of women"--Publicity materials. (PsycINFO Database Record (c) 2010 APA, all rights reserved)